Comparison of Intraoperative Nociception and Postoperative Acute Pain After Traditional or Minimally Invasive Ovariohysterectomy in Dogs - Minto, Bruno Watanabe; Filgueira, Fabrícia Geovânia Fernandes; de Alcântara, Brenda Mendonça; Sargi, Laís Fernanda; Magalhães Moi, Tryssia Scalon; Dias, Luis Gustavo Gosuen Gonçalves (Acta Scientiae Veterinariae, 2021)
Background: Many variations of ovariohysterectomy techniques have been described, including the traditional one and minimally invasive procedures. Non-laparoscopic Snook hook technique is an alternative for performing minimally invasive ovariohysterectomy. Few studies have been carried out in order to assess pain in animals submitted to minimally invasive surgeries, especially involving one of the most performed surgical procedures in veterinary practice. The aim of this study was to evaluate surgical duration, intraoperative nociception and acute postoperative pain after traditional ovariohysterectomy or minimally invasive non-laparoscopic technique in dogs using Snook hook. The hypothesis is that non-laparoscopic minimally invasive ovariohysterectomy would be faster and less painful than the conventional technique. Material, Methods & Results: Thirty dogs were divided into Traditional Group (TG = 15) and Minimally Invasive Group (MIG = 15). Heart rate, respiratory rate, systolic blood pressure, body temperature, oxyhemoglobin saturation, end-tidal carbon dioxide concentration (ETCO2) and end-tidal isoflurane concentration were evaluated before the surgery to start (M0), during incision (M1), clamping of the first ovarian pedicle (M2), second ovarian pedicle (M3), uterine cervix (M4), abdominal suture (M5) and at the end of surgery (M6). The modified Glasgow Pain Scale was used for acute postoperative pain assessment and Visual Analogue Scale (VAS) was used to assess the sensitivity of surgical wound. The level of significance established for all statistical analyzes was 5%. Statistical differences were not observed between groups considering total surgical time and postoperative acute pain intensity (P > 0.05), in spite of MIG having shorter duration of surgery. There was no statistical difference between groups considering all intraoperative parameters except respiratory rate (TG < MIG; P < 0.05) and ETCO2 (MIG < TG; P < 0.05) at the moment of traction of the first ovarian pedicle (M2). Pain assessment by VAS showed statistical difference 24h after the end of surgery (TG < MIG) (P < 0.05). Discussion: Both procedures were similar regarding intraoperative nociception and acute postoperative pain. It is possible that the sensation of pain in both procedures was blocked by the effectiveness of analgesics, once they might cause an inhibition of painful behaviors limiting a possible difference in pain identification. Higher respiratory stress observed in MIG at M2 and higher pain score by VAS noted in MIG 24 h after the end of surgery can be justified by greater traction of ovarian pedicle, due to limited surgical access of minimally invasive technique. Minimally invasive ovariohysterectomy non-laparoscopic seems to be potentially faster, probably due to the smaller size of the abdominal incision, which takes less time to be closed. In the present study, both techniques were performed by an experienced surgeon, providing safe procedures, nevertheless it is important to emphasize that iatrogenic injury can be caused by surgeons not proficient in the Snook hook technique, considering the limited visualization of anatomical abdominal structures. Data obtained indicate that traditional ovariohysterectomy and non-laparoscopic Snook hook technique promote similar intraoperative nociception and acute postoperative pain, however minimally invasive procedure is potentially faster and with less surgical trauma.